Reimagining Coolie Trajectories: The Triumphant Return as Political Statement in Late Qing "Coolie Fiction". Issue 5 (May 2016) - Weber, Elizabeth E.
Abstract: The trade in indentured Chinese labor (the "coolie trade") to the Americas was an exploitative labor‐recruitment regime that resulted in the transportation of over 300, 000 Chinese men to various work sites in the mid‐to‐late 19th century. As Chinese impacted either directly or indirectly by the trade attempted to process and comprehend the multiple violences they were witnessing and experiencing, there emerged what I have previously called "conceptual vocabularies" related to the trade – new terminologies, worldviews, and sense of geopolitical/racial position – as evidenced in contemporary media and official reportage. The following discussion will identify how the traumatic translocation of coolie laborers, having already given rise to these vocabularies, could go on in later years to inspire a small burst of "coolie fiction." With origins in Shanghai's Anti‐American Boycott of 1905, two such pieces of fiction — Bitter Society (1905) and Golden World (1907) (Ku shehui/Huangjin shijie 1985)— make use not just of the powerful latent vocabularies of the historic coolie trade but use the vari‐directional travels of the coolie protagonists as spatial metaphors for the characters' awakening activist subjectivity. The outward journey under the oppressive management of foreign recruiters symbolized China's loss of autonomy and humiliating descent into semicoloniality; while the triumphant depiction of erstwhile laborers returning from abroad to lead activist efforts as depicted in each novel can be read as a plea to readers to stand together and reclaim whatever power they could – whether from Euro‐American colonizers or from the "corrupt" Manchu ruling apparatus – in order to effect China's own "return" from its perilous state of semicoloniality. In making use of the coolie trade vocabularies and the coolie trajectories specifically, the novels simultaneously nod to a shared sense of past victimization and to the potential that such powerful public memory has to inspire social or political change.